Environmental factors that impact the eating behavior of home-living older adults - Fifi Kvalsvik; Torvald Øgaard; Øystein Jensen (Elsevier, 2021)
Objective: To identify environmental factors that influence the eating behavior of home-living older adults. Design: Qualitative study with two interview methods, dyadic and in-depth individual interviews. Setting: The study was conducted in a western district of Norway. Participants: A total of 22 participants. The study sample consisted of 8 dyads for the dyadic interviews and 6 participants for the in-depth individual interviews. The dyads were composed of pairs who share a pre-existing relationship as well as pairs of strangers. Method: The qualitative study uses deductive and inductive content analysis. Results: Seven environmental factors that play a role in older adults' eating behavior were organized into three levels of influence: interpersonal influence (food habits of significant others, household composition, and social relationship), community influence (senior centers and food access), and public policy influence (health information and transportation/mobility aids). Conclusion: Various environmental factors determine the eating behavior of older adults living at home. An approach is needed to address these factors in order to bring positive change in the eating behavior of home-living older adults. The findings suggest that a social environment may be used to encourage healthy eating. Furthermore, increasing participation in a senior center, ensuring access to food, reducing ambiguity in diet and nutrition information, and increasing mobility support can help older adults maintain or develop healthy eating behavior.